Post-traumatic effects of phosphorus weapons: from pathogenesis to treatment (Environment & Health, 2024)
With the beginning of a full-scale war, the negative impact of harmful, dangerous substances due to the use of chemical, phosphorus bombs and other weapons, prohibited by the GenevaConvention, leads to unpredictable consequences for the health of combatants and the civilian population as well.Objectives of the study is to analyze injuries caused by white phosphorus of various types of phosphorus weapons, such as explosive weapons with a wide area of damage - mines, ammunition, long-range missiles; artillery, mortar shells, various types of grenades - in the conditions of the russian invasion of Ukraine.Materials and methods. The following methods were used when performing the work: content analysis, comparative analysis and systematization of the researched material. A study of scientific publications of domestic and foreign scientists was conducted using the PubMed and Google Scholar databases for the period 2001-2023.The results. Phosphorus munitions such as white phosphorus are known for their high effectiveness in combat operations, but their use leads to serious injuries and post-traumatic psychological changes. White phosphorus after a bomb explosion causes burns to the tissues of the human body, especially when in contact with burning material, as well as burns to the upper respiratory tract due to inhalation of smoke or gases released during combustion.The article analyzes the legal framework prohibiting the use of phosphorous ammunition in armed conflicts. Clinical cases of combined gunshot wounds of the limbs with a massive defect of soft tissues, gunshot fractures and the presence of multiple foreign bodies of metallic density due to the used phosphorous ammunition were considered. An analysis of scientific research by foreign scientists on this issue was carried out. The article presents the algorithms for providing first aid due to the effects of phosphorous ammunition, as well as the methodological recommendations of the Ministry of Health of Ukraine (Order of the Ministry of Health of Ukraine № 506 dated 20.03.2022) regarding the provision of medical assistance at the pre-hospital stage for burns, enteral poisoning, and eye contact phosphorus as a result of damage by the phosphorus component of the ammunition.
Keywords: white phosphorus; phosphorus munitions; burn treatment; military actions